Association between Diurnal Temperature Range, Daily Mean Temperature and Sarcopenia States in Older Adults: Evidence from the CHARLS - Yang Zhong; Suyuan Wang; Doudou Hao; Suyin Zhu; Yanli Chen; Zhiyou Shi; Qing Yang; Yunhong Wu (BMC Geriatrics)
Abstract Background With growing concern about global climate change and its potential consequences, its health impacts have been widely studied. However, the association between temperature and sarcopenia states in Chinese older adults remains unclear. The study aimed to examine the association based on a nationally representative large-scale survey. Methods The study used data from three waves (2011, 2013, 2015) of the China Health and Retirement Longitudinal Study (CHARLS) for adults aged ≥ 60 years, combined with meteorological and PM2.5 data from the China Research Data Services (CNRDS) Platform (2011–2015). Sarcopenia states were assessed using the Asian Working Group for Sarcopenia criteria 2019 (AWGS2019). Cross-sectional analysis used generalized additive models with cubic splines to identify non-linear relationships between temperature and sarcopenia states prevalence. For longitudinal analysis, four multivariable logistic regression models were developed to assess the association, adjusting for confounders. Subgroup analyses evaluated population sensitivity to temperature exposure. Results The prevalence of possible sarcopenia was 29.4%, 28.5%, and 24.8% in 2011, 2013, and 2015, respectively, while sarcopenia rates were 9.6%, 10.7%, and 9.8%. Cross-sectional analysis showed that possible sarcopenia was associated with a higher risk of falls (OR: 1.31, P < 0.001) and hip fractures (OR: 1.63, P < 0.001). Longitudinal analysis revealed that a 1℃ increase in the three-year average diurnal temperature range (mDTR) raised the risk of possible sarcopenia by 8% (OR: 1.08, 95% CI: 1.01–1.15) and sarcopenia by 13% (OR: 1.13, 95% CI: 1.01–1.26). Conversely, a 1℃ increase in the three-year average daily mean temperature (mDMT) within 0–25℃ reduced the risk of possible sarcopenia by 4% (OR: 0.96, 95% CI: 0.94–0.99). Individuals living at altitudes ≥ 500 m were more vulnerable to the adverse effects of temperature fluctuations on possible sarcopenia. Conclusions Our study found that temperature is associated with sarcopenia states in Chinese older adults. Increased mDTR raised the risk of possible sarcopenia and sarcopenia, while mDMT (0–25℃) lowered possible sarcopenia risk. Individuals living at altitudes ≥ 500 m were more vulnerable to the adverse effects of temperature fluctuations on sarcopenia.